Differential equation of a fractal electrode?electrolyte interface - Felice, Carmelo Jose (2016)
Understanding an electrode-electrolyte interface (EEI) behavior is a valuable tool in several areas of science. There are models based on discrete fractal structures, which explain the measurements of linear and non-linear impedance at fixed frequencies, or at determined ranges of high and low current densities. A level by level discrete calculation is needed to evaluate these models, or the use of black-box models, which affect the good understanding of the phenomenon. A continuous model based on a differential equation of an EEI is presented in this paper. It includes an electrical circuit similar to a long transmission line. It has been deduced from the discrete Liu model.